Complete conditioning for tennis - Kovacs, Mark; Roetert, Paul; Ellenbecker, Todd S. 1962-; Roetert, Paul (Champaign, IL Human Kinetics, 2016)
Improve shot power, increase on-court speed and agility, and outlast the opposition with Complete Conditioning for Tennis! The only strength and conditioning resource endorsed by the United States Tennis Association, Complete Conditioning for Tennis details how to maximize your training with exercise, drills, and programs that do the following: Improve footwork and agility; increased speed and quickness; enhanced stamina; Increase flexibility; Reduce recovery time; Prevent common injuries; Assess physical strengths and deficiencies. Throughout, you will have access to the same recommendations and routines used by today's top professional players. From increasing the speed and power of your serve and groundstrokes to enhancing on-court agility and stamina, you will be ready to take the court with confidence and endure even the most grueling matches. Off the court, you'll learn recovery techniques and preventive exercises for keeping shoulder and elbow injuries at bay. Featuring more than 200 drills and exercises combined with exclusive online access to 55 video clips, Complete Conditioning for Tennis is an essential resource for players, coaches, instructors, and anyone serious about the sport
Chapter 1 Meeting the physical demands of tennis -- Chapter 2 Muscles and tennis strokes -- Chapter 3 Muscles and movements -- Chapter 4 High-performance fitness testing -- Chapter 5 Dynamic warm-up and flexibility -- Chapter 6 Speed, agility, and footwork -- Chapter 7 Core stability training -- Chapter 8 Strength training -- Chapter 9 Power training -- Chapter 10 Tennis endurance training -- Chapter 11 Program design and periodization -- Chapter 12 Solid shoulder stability -- Chapter 13 Injury prevention and rehabilitation -- Chapter 14 Nutrition and hydration -- Chapter 15 Recovery -- Chapter 16 Age and gender considerations
Includes index
Revised edition of: Complete conditioning for tennis / E. Paul Roetert, Todd S. Ellenbecker. 2007
"Includes access to online video library" -- Bookcover
Keywords: Tennis -- Training